STORYTELLING TO INCREASE EARLY CHILDHOOD RESPONSIBILITY IN RA AR-RAIHAN - Nada, Aulia Qatrun; Karyawati, Lilis Qatrun (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2025)
An attitude of responsibility is one of the important aspects in the formation of early childhood character which is generally formed through the process of observing, imitating, and habituating in the family, school, and play environment. Initial observations at RA Ar-Raihan show that there are still many children who have not displayed responsible behavior, such as tidying up toys after use, completing tasks to completion, putting things back in their place, and daring to admit mistakes. Based on these problems, this research aims to improve children's attitude of responsibility through the application of the storytelling method. The research uses the PTK approach which is carried out in two cycles, with each cycle including planning, implementation, observation, and reflection. Data was collected through observation and analyzed using qualitative descriptive analysis techniques. The results of the study showed a significant increase in the development of children's responsible attitudes. In the initial condition, most children are still in the category of "not yet developed" or "starting to develop". After cycle I, there was an increase to the categories of "progressing as expected" and "progressing very well". In cycle II, the results were more optimal, characterized by the absence of children who were in the "undeveloped" category. Thus, it can be concluded that the application of the storytelling method is effective in increasing the attitude of responsibility in early childhood, as well as making a practical contribution for teachers in integrating character values through fun and contextual learning strategies.